STATUS KEPEMILIKAN LAHAN DAN MODAL SOSIAL DESA PATENGAN DAN DESA ALAM ENDAH KECAMATAN RANCABALI KABUPATEN BANDUNG SELATAN - Muthiah, Jadda; Muntasib, E. K. S. Harini; Meilani, Resti; Sunkar, Arzyana; Rahayuningsih, Tri (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Patengan and Alam Endah villages located in the Rancabali District South Bandung. Both villages have identical characteristics to the region that most of the people engaged in agricultural with variations in the tourism sector. The identical characteristic make social capital comparation can be done. Differences in the two villages is contained in land tenure wich unlike Alam Endah Village that have private land tenure, Patengan Village are in state land tenure. The field research was conducted in June 2016. The depth interviews were conducted using a semi-structured questioner developed by Social Capital Assessment Tool (SCAT). Research is done by carefully observing the phenomenon using participant observation approach. Research showed that land tenure have effect on social capital (especially on trust, norm, caring and proactive action element) which happened because public concern over restrictions on access to natural resources increase the value of social capital because people tend to give positive responses to avoid conflict. In contrary, a figure that have influence toward natural resources access followed by other society member makes social capital inevitable increase. Key word: Alam Endah Village, land tenure, Patengan Village, social capital